2011
DOI: 10.1186/1472-6939-12-23
|View full text |Cite
|
Sign up to set email alerts
|

Nurse managers' experience with ethical issues in six government hospitals in Malaysia: A cross-sectional study

Abstract: BackgroundNurse managers have the burden of experiencing frequent ethical issues related to both their managerial and nursing care duties, according to previous international studies. However, no such study was published in Malaysia. The purpose of this study was to explore nurse managers' experience with ethical issues in six government hospitals in Malaysia including learning about the way they dealt with the issues.MethodsA cross-sectional study was conducted in August-September, 2010 involving 417 (69.2%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…From the above strategies and action taken, it was clear that managers tried to manage any incident or issues internally or reported the matter to the higher nursing administration team for further action. This was similar to a study in Malaysia that stated nurse managers usually relied on three things in managing ethical issues: their skills, the management team or other nurses, or the code of ethics, but in most cases, the latter was the least preferred (19).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…From the above strategies and action taken, it was clear that managers tried to manage any incident or issues internally or reported the matter to the higher nursing administration team for further action. This was similar to a study in Malaysia that stated nurse managers usually relied on three things in managing ethical issues: their skills, the management team or other nurses, or the code of ethics, but in most cases, the latter was the least preferred (19).…”
Section: Discussionsupporting
confidence: 80%
“…Such issues may create a stressful working environment for the nurses, patients, relatives, and other healthcare providers, including the nurse managers. The stressor may also be higher in nurse managers as they are involved in patient care and have supervision responsibilities to their subordinates and management responsibilities to the higher authority (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, a study evaluated the ethical issues experienced by 417 nursing managers employed in six of the country’s hospitals The information obtained revealed that most managers, regardless of their area of practice, experienced many ethical issues and described how they handled problems. A team approach and an adequate understanding of the code of ethics as the basis for reasoning 12 is needed to deal with ethical issues.…”
Section: Discussionmentioning
confidence: 99%
“…An ethical dilemma is a problem in the decisionmaking process between two possible options, neither acceptable from an ethical perspective. According to a recent international study, nurses face a variety of ethical dilemmas (2)(3)(4)(5), including nurses in Malaysia (6,7). Numerous strategies employed by nurses to address and resolve ethical dilemmas were recognised, including the use of the ethical framework (8,9), code of professional ethics (10)(11)(12), and some underscore the ethical values alone, which have been established in the literature review (13,14).…”
Section: Introductionmentioning
confidence: 99%